Analisis Big Data terhadap Pembentukan Narasi Demo Tiga Periode : Studi Analitik Tekstual pada Media Berita Tempo - Kurniawan, Ahmad Rizki; Setiawan, Adhitya Widyadhana; Fadlurrahman, Anis Satrio; Putri, Noviasih Natika (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2023)
The end of the new order era gave a welcome to the reform era in increasing the flow of democracy, one of which is freedom of the press, which in the context of this study is the news about the formation of the narrative of Jokowi's three-period demonstration. The research was conducted using the textual network analysis method, to see how the tempo media's role in reporting narratives related to the three-period demo. The results of network mapping on narrative analysis in the tempo media provide four main narratives consisting of the extension of the presidential period, the role of students in the formation of the narrative of the government period, the correlation of society to the government, and the correlation of the student executive body to the government.